A coolant resistant glass fiber reinforced pa material and method of making same

CN122978699APending Publication Date: 2026-10-27SUZHOU SUNWAY POLYMER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611213954.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]常规玻璃纤维增强PA在高温乙二醇水溶液中长期使用时,通常存在两个相互独立但又相互促进的失效过程:其一,水分进入PA基体后使酰胺键发生水解,导致聚合物分子量下降,进而引起材料强度和韧性降低;其二,冷却液沿PA与玻璃纤维的界面渗入,使界面结合强度下降并发生玻璃纤维与基体脱粘

Benefits of technology

1、本发明通过采用氨基端基含量大于羧基端基含量的端氨基PA66,可降低羧基端基在高温含水介质中对酰胺键水解的促进作用,并利用氨基端基对体系中的酸性物质进行反应或中和,从基体侧减缓PA66分子量下降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The application provides a cooling liquid resistant glass fiber reinforced PA material and a preparation method thereof, which comprises amino-terminated PA66, reactive interface modified glass fiber, antioxidant and nucleating agent, the content of amino end groups in the amino-terminated PA66 is greater than the content of carboxyl end groups; the surface of the reactive interface modified glass fiber has an epoxy-containing silane coupling layer and a polyamide layer from inside to outside, the polyamide layer is formed by the reaction of double carboxyl-terminated oligomer PA66 and epoxy groups in the epoxy-containing silane coupling layer and retains carboxyl groups. The amino-terminated PA66 with the content of amino end groups greater than the content of carboxyl end groups is used to reduce the promoting effect of carboxyl end groups on the hydrolysis of amide bonds in a high-temperature aqueous medium, and the amino end groups are used to slow down the decrease of the molecular weight of PA66 from the side of the matrix; meanwhile, the outermost oligomer PA66 layer of the glass fiber can improve the interface compatibility, and the retained carboxyl groups can react and combine with the amino end groups of the amino-terminated PA66 in the melting process, thereby reducing the interface debonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a coolant-resistant glass fiber reinforced PA material and its preparation method. Background Technology

[0002] Glass fiber reinforced polyamide (also known as nylon, abbreviated as PA) has high strength, rigidity, heat resistance, and dimensional stability, and can be used in radiator end slots, coolant pipe joints, thermostat housings, water pump housings, and coolant contact components in the thermal management systems of new energy vehicles. These components are in prolonged contact with coolant containing ethylene glycol and water during use and may be exposed to high temperature and pressure environments.

[0003] When conventional glass fiber reinforced polyamide (PA) is used long-term in high-temperature ethylene glycol aqueous solutions, two independent but mutually reinforcing failure processes typically occur: First, moisture entering the PA matrix hydrolyzes the amide bonds, leading to a decrease in polymer molecular weight and consequently reducing material strength and toughness. Second, coolant penetrates along the PA-glass fiber interface, reducing interfacial bonding strength and causing debonding of the glass fibers from the matrix. Interfacial penetration increases the contact area between the coolant and PA, while the hydrolysis of the PA matrix reduces its ability to encapsulate and constrain the glass fibers; therefore, the two failure processes mutually promote each other. Summary of the Invention

[0004] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a coolant-resistant glass fiber reinforced PA material and its preparation method. By using a PA66 matrix with amino-terminated groups, and setting an epoxy-containing silane coupling layer and a carboxyl-retaining oligomeric PA66 layer on the glass fiber surface, the hydrolysis of the PA66 matrix and the debonding of the glass fiber interface are slowed down. This solves the problems of PA66 matrix hydrolysis and glass fiber interface debonding caused by high-temperature coolants in the prior art.

[0005] To achieve the above and other related objectives, the present invention provides the following technical solutions: In a first aspect, the present invention provides a coolant-resistant glass fiber reinforced PA material, comprising, by weight: 60-70 parts of amino-terminated PA66, 30-40 parts of reactive interface-modified glass fiber, 0.2-0.8 parts of antioxidant, and 0.1-0.3 parts of nucleating agent; The content of amino terminal groups in the terminal amino PA66 is greater than the content of carboxyl terminal groups; The surface of the reactive interface-modified glass fiber has an epoxy-containing silane coupling layer and a polyamide layer from the inside to the outside. The polyamide layer is formed by the reaction of dicarboxyl-terminated oligomeric PA66 with epoxy groups in the epoxy-containing silane coupling layer. The polyamide layer retains carboxyl groups that can react with the amino end groups of the terminal amino group PA66.

[0006] Furthermore, the amino end group content in the terminal amino PA66 is 65~95 μmol / g, and the carboxyl end group content is 12~35 μmol / g.

[0007] Furthermore, the ratio of amino terminal group content to carboxyl terminal group content in the terminal amino PA66 is (2.0~6.0):1.

[0008] Furthermore, the relative viscosity of the terminal amino group PA66 measured at 25°C in a 96% sulfuric acid solution with a mass concentration of 1.0 g / dL is 2.3–3.0.

[0009] Furthermore, the number-average molecular weight of the dicarboxyl-terminated oligomeric PA66 is 1500–3500 g / mol, and the acid value is 35–75 mg KOH / g.

[0010] Furthermore, the glass fiber is alkali-free E glass fiber or ECR glass fiber, with a single filament diameter of 10-13 μm and a chopped length of 3-5 mm.

[0011] Furthermore, the epoxy-containing silane with the epoxy-containing coupling layer is selected from γ-glycidoxypropyltrimethoxysilane.

[0012] Furthermore, the antioxidants include hindered phenolic antioxidants and phosphite antioxidants.

[0013] Furthermore, the nucleating agent is selected from sodium phenylphosphinate.

[0014] Furthermore, the coolant-resistant glass fiber reinforced PA material also includes 0.1 to 0.4 parts of a lubricant, wherein the lubricant is calcium lignite.

[0015] Furthermore, the coolant-resistant glass fiber reinforced PA material also includes 0 to 0.50 parts of colorant.

[0016] A second aspect of the present invention provides a method for preparing the above-mentioned coolant-resistant glass fiber reinforced PA material, comprising the following steps: S1. Preparation of reactive interface-modified glass fibers; S2. Components other than reactive interface-modified glass fiber are added from the main feed port of the twin-screw extruder. After the terminal amino PA66 melts, the reactive interface-modified glass fiber is added from the side feed port, so that the remaining carboxyl groups in its polyamide layer react with the amino end groups of the terminal amino PA66. Vacuum degassing is performed downstream of the location where the reactive interface-modified glass fiber is added. S3. The extruded molten material is stretched, cooled, and pelletized to obtain a coolant-resistant glass fiber reinforced PA material.

[0017] Further, step S1 includes: hydrolyzing an epoxy-containing silane and coating it onto the surface of a glass fiber and performing a first drying to obtain epoxy-containing silane-treated glass fiber; coating a dispersion containing dicarboxyl-terminated oligomeric PA66 onto the surface of the epoxy-containing silane-treated glass fiber, performing a second drying and pre-reaction to allow some carboxyl groups to react with epoxy groups while retaining the other part of the carboxyl groups, to obtain reactive interface-modified glass fiber.

[0018] Furthermore, the hydrolysate containing epoxy silane has an epoxy silane mass fraction of 0.5%–1.5%, a pH of 4.0–5.0, and a hydrolysis time of 20–40 min.

[0019] Furthermore, the solid content of the dispersion containing dicarboxyl-terminated oligomeric PA66 is 8% to 15%, and the dicarboxyl-terminated oligomeric PA66 accounts for 80% to 92% of the dry matter of the dispersion.

[0020] Furthermore, the temperature of the second drying is 110–130°C, and the temperature of the pre-reaction is 160–185°C for 2–8 minutes.

[0021] Further, in step S2, the melt temperature of the twin-screw extruder is 260–280°C, the screw speed is 250–600 r / min, and the vacuum degree is… 0.080~ 0.095 MPa, melt residence time is 45-100 s.

[0022] A third aspect of the present invention provides a coolant-resistant molded part, which is injection molded from the aforementioned coolant-resistant glass fiber reinforced PA material. The coolant-resistant molded part is a radiator end slot, a coolant pipe joint, a thermostat housing, a water pump housing, or a coolant contact component in the thermal management system of a new energy vehicle.

[0023] As described above, the coolant-resistant glass fiber reinforced PA material and its preparation method of the present invention have the following beneficial effects: 1. This invention uses PA66 with a higher content of amino terminal groups than carboxyl terminal groups, which can reduce the promoting effect of carboxyl terminal groups on the hydrolysis of amide bonds in high-temperature aqueous media, and utilize amino terminal groups to react with or neutralize acidic substances in the system, thereby slowing down the decrease in the molecular weight of PA66 from the matrix side.

[0024] 2. This invention prepares reactive interface-modified glass fibers. An epoxy-containing silane coupling layer first forms a stable bond with the glass fiber surface. A portion of the carboxyl groups in the dicarboxyl-terminated oligomeric PA66 then reacts with the epoxy groups, fixing the oligomeric PA66 layer onto the glass fiber surface. The oligomeric PA66 layer and the PA66 matrix have the same repeating structure, improving interfacial compatibility. The carboxyl groups retained in the oligomeric PA66 layer can react with the amino end groups of the amino-terminated PA66 during melt blending, further bonding the organic layer on the glass fiber surface with the PA66 matrix, thereby reducing coolant penetration along the glass fiber interface and interfacial debonding. The matrix end-group control and the interfacial reaction layer target two failure processes respectively, jointly improving the material's performance retention after aging.

[0025] 3. The reactive interface-modified glass fiber of the present invention is added by side feeding, which can reduce excessive shearing of glass fiber during extrusion; and vacuum degassing is performed downstream of the side feeding position to remove residual moisture in the raw materials and water generated by the interface reaction, thereby reducing the risk of hydrolytic degradation of PA66 during processing. Detailed Implementation

[0026] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. It should be noted that, unless otherwise specified, the following embodiments and features described herein can be combined with each other.

[0027] The main ingredients are as follows: Amino-terminated PA66-A: amino terminus 80 μmol / g; carboxyl terminus 20 μmol / g; relative viscosity 2.65.

[0028] Amino-terminated PA66-B: Amino terminal group 68 μmol / g; Carboxyl terminal group 32 μmol / g; Relative viscosity 2.35.

[0029] Amino-terminated PA66-C: amino terminus 90 μmol / g; carboxyl terminus 16 μmol / g; relative viscosity 2.95.

[0030] Standard PA66: 45 μmol / g amino terminal group; 45 μmol / g carboxyl terminal group; relative viscosity 2.65.

[0031] Dicarboxylated end-capped oligomer PA66-1: number average molecular weight 2500 g / mol; acid value 52 mg KOH / g.

[0032] Dicarboxylated end-capped oligomer PA66-2: number average molecular weight 1600 g / mol; acid value 72 mg KOH / g.

[0033] Dicarboxylated end-capped oligomer PA66-3: number average molecular weight 3400 g / mol; acid value 36 mg KOH / g.

[0034] Glass fiber (GF): ECR continuous glass fiber without organic impregnation agent; single filament diameter 10-13 μm.

[0035] Antioxidants: hindered phenolic antioxidant 1098 and phosphite antioxidant 168.

[0036] Nucleating agent: Sodium phenylphosphinate.

[0037] Lubricant: Calcium lignite.

[0038] PA66, with its amino-terminated groups, is prepared by using adipic acid and hexamethylenediamine as monomers, through salt formation and melt polycondensation. In preparing the PA66 salt solution, hexamethylenediamine is used as an end-group regulator to maintain a predetermined molar excess of hexamethylenediamine relative to adipic acid in the reaction system. Subsequently, the PA66 salt solution is added to the polymerization reactor, and pre-polymerization is carried out under pressure under nitrogen protection. The temperature is then increased and the pressure is gradually released to atmospheric pressure, followed by depressurization polymerization. By adjusting the excess amount of hexamethylenediamine and the depressurization polymerization time, the amino-terminated group content, carboxyl-terminated group content, and relative viscosity of the resulting PA66 are controlled.

[0039] The amino and carboxyl end-group contents of PA66 were determined by potentiometric titration and expressed as a basis based on the mass of dried resin. The relative viscosity was tested at 25°C, with a PA66 mass concentration of 1.0 g / dL and 96% sulfuric acid as the solvent.

[0040] Dicarboxylated terminal oligomer PA66 can be prepared by prepolymerization of PA66 with excess adipic acid. Taking dicarboxylated terminal oligomer PA66-1 as an example, adipic acid and hexamethylenediamine are added to a reactor at a molar ratio of 1.10:1, followed by deionized water accounting for 30% of the total monomer mass. The mixture is heated to 210℃ under nitrogen protection and reacted at 1.5–1.8 MPa for 60 min; then the temperature is raised to 245℃ and the pressure is gradually released to atmospheric pressure over 45 min, followed by... The reaction was carried out at 0.085 MPa for 20 min, followed by cooling and pulverization. The dicarboxylated terminal oligomer PA66-1 with the above-mentioned number-average molecular weight and acid value was obtained by controlling the reaction endpoint. Dicarboxylated terminal oligomer PA66-2 and dicarboxylated terminal oligomer PA66-3 were prepared by the same method, and the number-average molecular weight and acid value were controlled by increasing the excess ratio of adipic acid and shortening the reaction time, or decreasing the excess ratio of adipic acid and extending the reaction time, respectively.

[0041] The number-average molecular weight of dicarboxylated end-capped oligomer PA66 was determined by gel permeation chromatography, and the acid value was determined by potassium hydroxide titration.

[0042] Example 1 This embodiment provides a coolant-resistant glass fiber reinforced PA material, which, by weight, comprises: 64 parts of amino-terminated PA66-A, 35 parts of reactive interface-modified glass fiber G1, 0.25 parts of hindered phenolic antioxidant 1098, 0.25 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, and 0.20 parts of calcium lignite.

[0043] Its preparation method includes the following steps: S1. Preparation of reactive interface-modified glass fiber G1: γ-glycidoxypropyltrimethoxysilane was added to deionized water, and the pH was adjusted to 4.5 using acetic acid. Hydrolysis was carried out at room temperature for 30 minutes to obtain a hydrolysate with a silane mass fraction of 1.0%. The hydrolysate was uniformly coated onto the surface of the glass fiber at a ratio of 60 g of hydrolysate per kilogram of glass fiber, and then dried for the first time at 110°C for 12 minutes.

[0044] Dicarboxyl-terminated oligomer PA66-1, fatty alcohol polyoxyethylene ether nonionic dispersant, and polyethylene glycol were added to deionized water at a dry matter mass ratio of 88:8:4. After high-speed dispersion and homogenization, an oligomer PA66 dispersion with a solid content of 12% was prepared. The dispersion was uniformly coated onto the surface of the glass fiber after the first drying at a ratio of 80g of dispersion per kilogram of glass fiber. The fiber was then dried a second time at 120℃ for 12min, followed by a pre-reaction at 170℃ for 5min. After cooling, the fiber was chopped to 4.5mm to obtain reactive interface-modified glass fiber G1.

[0045] S2. The terminal amino group PA66-A was vacuum-dried at 100℃ for 8 h to achieve a moisture content not exceeding 0.06%; the reactive interface-modified glass fiber G1 was dried at 120℃ for 3 h. The terminal amino group PA66-A was mixed evenly with all additives except G1, and then fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1. The temperatures of each zone of the extruder were 250℃, 260℃, 268℃, 272℃, 275℃, 272℃, and 268℃, respectively, with a melt temperature of 270℃ and a screw speed of 350 r / min. After the terminal amino group PA66-A melted, G1 was added through the side feed port, and vacuum degassing was performed downstream of the side feed port to a vacuum level of [missing information]. 0.090 MPa, melt residence time approximately 70 s.

[0046] S3. After the melt is extruded through a die, drawn into strips, water-cooled and pelletized, it is vacuum dried at 100℃ for 6 h to obtain a coolant-resistant glass fiber reinforced PA material 1.

[0047] Example 2 This embodiment provides a coolant-resistant glass fiber reinforced PA material, which, by weight, comprises: 68.5 parts of amino-terminated PA66-B, 30.5 parts of reactive interface-modified glass fiber G2, 0.25 parts of hindered phenolic antioxidant 1098, 0.25 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, and 0.20 parts of calcium lignite.

[0048] Its preparation method includes the following steps: S1, Preparation of reactive interface-modified glass fiber G2: γ-glycidoxypropyltrimethoxysilane was added to deionized water, and the pH was adjusted to 4.0 using acetic acid. Hydrolysis was carried out at room temperature for 20 minutes to obtain a hydrolysate with a silane mass fraction of 0.5%. The hydrolysate was uniformly coated onto the surface of the glass fiber at a ratio of 60 g of hydrolysate per kilogram of glass fiber, and then dried for the first time at 110°C for 12 minutes.

[0049] Dicarboxyl-terminated oligomer PA66-2, fatty alcohol polyoxyethylene ether nonionic dispersant, and polyethylene glycol were added to deionized water at a dry matter mass ratio of 80:12:8. After high-speed dispersion and homogenization, an oligomer PA66 dispersion with a solid content of 8% was prepared. The dispersion was uniformly coated onto the surface of the glass fiber after the first drying at a ratio of 80g of dispersion per kilogram of glass fiber. The fiber was then dried a second time at 110℃ for 12min, followed by a pre-reaction at 160℃ for 2min. After cooling, the fiber was chopped to 3.0mm to obtain reactive interface-modified glass fiber G2.

[0050] S2. Terminally amino-terminated PA66-B was vacuum-dried at 100℃ for 8 h to achieve a moisture content not exceeding 0.06%; reactive interface-modified glass fiber G2 was dried at 120℃ for 3 h. The terminally amino-terminated PA66-B was mixed evenly with all additives except G2, and then fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1. The extruder temperatures in each zone were 250℃, 260℃, 268℃, 272℃, 275℃, 272℃, and 268℃, respectively, with a melt temperature of 270℃ and a screw speed of 250 r / min. After the terminally amino-terminated PA66-B melted, G2 was added through the side feed port, and vacuum degassing was performed downstream of the side feed port to a vacuum level of [missing information]. 0.080 MPa, melt residence time approximately 100 s.

[0051] S3. After the melt is extruded through a die, drawn into strips, water-cooled and pelletized, it is vacuum dried at 100℃ for 6 h to obtain a coolant-resistant glass fiber reinforced PA material 2.

[0052] Example 3 This embodiment provides a coolant-resistant glass fiber reinforced PA material, which, by weight, comprises: 60 parts of amino-terminated PA66-C, 39 parts of reactive interface-modified glass fiber G3, 0.30 parts of hindered phenolic antioxidant 1098, 0.30 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, 0.20 parts of calcium lignite, and 0.10 parts of carbon black.

[0053] Its preparation method includes the following steps: S1. Preparation of reactive interface-modified glass fiber G3: γ-glycidoxypropyltrimethoxysilane was added to deionized water, and the pH was adjusted to 5.0 using acetic acid. Hydrolysis was carried out at room temperature for 40 minutes to obtain a hydrolysate with a silane mass fraction of 1.5%. The hydrolysate was uniformly coated onto the surface of the glass fiber at a ratio of 60 g of hydrolysate per kilogram of glass fiber, and then dried for the first time at 110°C for 12 minutes.

[0054] Dicarboxyl-terminated oligomeric PA66-3, fatty alcohol polyoxyethylene ether nonionic dispersant, and polyethylene glycol were added to deionized water at a dry matter mass ratio of 92:6:2. After high-speed dispersion and homogenization, an oligomeric PA66 dispersion with a solid content of 15% was prepared. The dispersion was uniformly coated onto the surface of the glass fiber after the first drying at a ratio of 80g of dispersion per kilogram of glass fiber. The fiber was then dried a second time at 130℃ for 12min, followed by a pre-reaction at 185℃ for 8min. After cooling, the fiber was chopped to 5.0mm to obtain reactive interface-modified glass fiber G3.

[0055] S2. The terminal amino-terminated PA66-C was vacuum-dried at 100℃ for 8 h to achieve a moisture content not exceeding 0.06%; the reactive interface-modified glass fiber G3 was dried at 120℃ for 3 h. The terminal amino-terminated PA66-C was mixed evenly with all additives except G3, and then fed into the main feed port of a co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1. The temperatures of each zone of the extruder were 250℃, 260℃, 268℃, 272℃, 275℃, 272℃, and 268℃, respectively, with a melt temperature of 270℃ and a screw speed of 600 r / min. After the terminal amino-terminated PA66-C melted, G3 was added through the side feed port, and vacuum degassing was performed downstream of the side feed port to a vacuum level of [missing information]. 0.095 MPa, melt residence time approximately 45 s.

[0056] S3. After the melt is extruded through a die, drawn into strips, water-cooled and pelletized, it is vacuum dried at 100℃ for 6 h to obtain a coolant-resistant glass fiber reinforced PA material 3.

[0057] Comparative Example 1 This comparative example provides a glass fiber reinforced PA material, comprising, by weight: 64 parts of ordinary PA66, 35 parts of ordinary glass fiber GF, 0.25 parts of hindered phenolic antioxidant 1098, 0.25 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, and 0.20 parts of calcium lignite. The formulation and extrusion conditions of this comparative example are consistent with those of Example 1, except that terminal amino-terminated PA66 and bilayer reactive interface-modified glass fiber are not used.

[0058] Comparative Example 2 This comparative example provides a glass fiber reinforced PA material, comprising, by weight: 64 parts of amino-terminated PA66-A, 35 parts of ordinary glass fiber GF, 0.25 parts of hindered phenolic antioxidant 1098, 0.25 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, and 0.20 parts of calcium lignite. The formulation and extrusion conditions of this comparative example are consistent with those of Example 1, the only difference being that a bilayer reactive interface-modified glass fiber is not used.

[0059] Comparative Example 3 This comparative example provides a glass fiber reinforced PA material, comprising, by weight: 64 parts of ordinary PA66, 35 parts of reactive interface-modified glass fiber G1 prepared in Example 1, 0.25 parts of hindered phenolic antioxidant 1098, 0.25 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, and 0.20 parts of calcium lignite. The formulation and extrusion conditions of this comparative example are consistent with those of Example 1, the only difference being that terminal amino-terminated PA66 is not used.

[0060] Comparative Example 4 This comparative example provides a glass fiber reinforced PA material, which, by weight, comprises: 64 parts of amino-terminated PA66-A, 35 parts of silane-modified glass fiber, 0.25 parts of hindered phenolic antioxidant 1098, 0.25 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, and 0.20 parts of calcium lignite.

[0061] The silane-modified glass fiber is obtained by the following steps: γ-glycidoxypropyltrimethoxysilane is added to deionized water, the pH is adjusted to 4.5 using acetic acid, and hydrolyzed at room temperature for 30 min to obtain a hydrolysate with a silane mass fraction of 1.0%. The hydrolysate is uniformly coated onto the surface of the glass fiber at a ratio of 60 g of hydrolysate per kilogram of glass fiber, and dried for the first time at 110°C for 12 min. After cooling, it is cut to a length of 4.5 mm to obtain the silane-modified glass fiber.

[0062] The formulation and extrusion conditions of this comparative example are the same as those of Example 1, except that the glass fiber surface is only treated with epoxy silane hydrolysate and is not coated with dicarboxyl-terminated oligomeric PA66.

[0063] Comparative Example 5 This comparative example provides a glass fiber reinforced PA material, which, by weight, comprises: 64 parts of amino-terminated PA66-A, 35 parts of glass fiber coated only with dicarboxyl-terminated oligomeric PA66-1, 0.25 parts of hindered phenolic antioxidant 1098, 0.25 parts of phosphite antioxidant 168, 0.20 parts of sodium phenylphosphinate, and 0.20 parts of calcium lignite.

[0064] The glass fiber coated only with dicarboxyl-terminated oligomeric PA66-1 was obtained by the following steps: dicarboxyl-terminated oligomeric PA66-1, fatty alcohol polyoxyethylene ether nonionic dispersant, and polyethylene glycol were added to deionized water at a dry matter mass ratio of 88:8:4. After high-speed dispersion and homogenization, an oligomeric PA66 dispersion with a solid content of 12% was prepared. The dispersion was uniformly coated onto the surface of the glass fiber at a ratio of 80g of dispersion per kilogram of glass fiber. The fiber was dried at 120°C for 12 minutes, and then pre-reacted at 170°C for 5 minutes. After cooling, the fiber was chopped to 4.5mm to obtain the glass fiber coated only with dicarboxyl-terminated oligomeric PA66-1.

[0065] The formulation and extrusion conditions of this comparative example are the same as those of Example 1, except that the glass fiber surface is not treated with epoxy silane hydrolysate and is directly coated with dicarboxyl-terminated oligomeric PA66.

[0066] Comparative Example 6 This comparative example provides a glass fiber reinforced PA material. The only difference from Example 1 is that in step S2, the reactive interface modified glass fiber G1 is not vacuumed after being side-fed, while all other conditions are the same.

[0067] Performance testing The materials obtained in Examples 1-3 and Comparative Examples 1-6 were vacuum dried at 100°C for 6 hours to ensure a moisture content of no more than 0.08%, and then injection molded into standard samples. The samples were then conditioned at 23°C and 50% relative humidity for 48 hours before initial performance testing. The test items are as follows:

[0068] The aging medium for the coolant was prepared by mixing ethylene glycol and deionized water at a volume ratio of 50:50. The samples were completely immersed in a sealed, pressure-resistant container lined with polytetrafluoroethylene (PTFE). The ratio of the medium's mass to the total sample mass was not less than 10:1, and the liquid volume did not exceed 80% of the container's effective volume. The samples were aged at 135±2℃ for 500 h and 1000 h, respectively. After aging for 500 h, samples undergoing the 1000 h test were replaced with a freshly prepared medium.

[0069] After removal, the sample was quickly rinsed with deionized water to remove surface liquid, and then placed at 23°C and 50% relative humidity for 24 hours before being tested according to the above test items. The performance retention rate was calculated using the following formula: Performance retention rate (%) = Performance after aging / Performance before aging × 100%.

[0070] The test results are shown in Tables 1 and 2.

[0071] Table 1. Coolant Resistance Test Data

[0072] Table 2. Matrix degradation and interfacial bonding data

[0073] Test results show that by simultaneously controlling the amino end-group content of the PA66 matrix and the interfacial structure of the glass fiber surface, this invention can significantly improve the long-term mechanical property retention rate of glass fiber reinforced PA66 materials in high-temperature coolant environments. Compared with comparative examples using only amino-terminated PA66, only interface-modified glass fiber, and ordinary PA66 and ordinary glass fiber, the material of this invention exhibits higher tensile strength, notched impact strength, and interfacial shear strength retention rates after immersion in 135℃ coolant for 1000 h, while also showing lower mass change rate and melt volume flow rate increase. This indicates that this invention can simultaneously slow down the hydrolytic degradation of the PA66 matrix and the aging failure of the glass fiber / PA66 interface. The results of Example 1 and the comparative examples also show that there is a synergistic effect between the amino-terminated PA66 matrix and the bilayer interface-modified glass fiber.

[0074] In summary, this invention utilizes PA66 with a higher content of amino-terminal groups than carboxyl-terminal groups. This reduces the promoting effect of carboxyl-terminal groups on amide bond hydrolysis in high-temperature aqueous media. Furthermore, the amino-terminal groups react with or neutralize acidic substances in the system, slowing down the decrease in PA66 molecular weight from the matrix side. Simultaneously, the outermost oligomeric PA66 layer of the reactive interface-modified glass fiber has the same repeating structure as the PA66 matrix, improving interfacial compatibility. Moreover, the carboxyl groups retained in the oligomeric PA66 layer can react and bind with the amino-terminal groups of the amino-terminal PA66 during melt blending, reducing coolant penetration along the glass fiber interface and interfacial debonding. Therefore, this invention effectively overcomes the various shortcomings of existing technologies and has high industrial applicability.

[0075] The terms used in this specification, such as "upper," "lower," "left," "right," "front," "back," "middle," and "one," are merely for clarity of description and are not intended to limit the scope of the invention. Any changes or adjustments to their relative relationships, without substantially altering the technical content, shall also be considered within the scope of the invention.

[0076] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. All equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in this invention should still be covered by the claims of this invention.

Claims

1. A glass fiber reinforced PA material resistant to coolant, characterized in that, By weight, it includes: 0-70 parts of amino-terminated PA666, 30-40 parts of reactive interface-modified glass fiber, 0.2-0.8 parts of antioxidant, and 0.1-0.3 parts of nucleating agent; The content of amino terminal groups in the terminal amino PA66 is greater than the content of carboxyl terminal groups; The surface of the reactive interface modified glass fiber has an epoxy-containing silane coupling layer and a polyamide layer from the inside to the outside. The polyamide layer is formed by the reaction of dicarboxyl-terminated oligomeric PA66 with the epoxy groups in the epoxy-containing silane coupling layer, and the polyamide layer retains carboxyl groups that can react with the amino end groups of the terminal amino group PA66.

2. The coolant-resistant glass fiber reinforced PA material according to claim 1, characterized in that, The amino end group content of the terminal amino group PA66 is 65~95 μmol / g, and the carboxyl end group content is 12~35 μmol / g.

3. The coolant-resistant glass fiber reinforced PA material according to claim 2, characterized in that, The ratio of amino terminal group content to carboxyl terminal group content in the terminal amino PA66 is (2.0~6.0):

1.

4. The coolant-resistant glass fiber reinforced PA material according to claim 1, characterized in that, The dicarboxyl-terminated oligomeric PA66 has a number-average molecular weight of 1500–3500 g / mol and an acid value of 35–75 mg KOH / g.

5. The coolant-resistant glass fiber reinforced PA material according to claim 1, characterized in that, The glass fiber is alkali-free E glass fiber or ECR glass fiber, with a single filament diameter of 10-13 μm and a chopped length of 3-5 mm; the epoxy-containing silane in the epoxy-containing silane coupling layer is selected from γ-glycidoxypropyltrimethoxysilane.

6. The coolant-resistant glass fiber reinforced PA material according to claim 1, characterized in that, The antioxidants include hindered phenolic antioxidants and phosphite antioxidants; the nucleating agent is selected from sodium phenylphosphinate; the coolant-resistant glass fiber reinforced PA material also includes 0.1 to 0.4 parts of a lubricant, wherein the lubricant is calcium lignite.

7. A method for preparing a coolant-resistant glass fiber reinforced PA material, characterized in that, Includes the following steps: S1. Preparation of reactive interface-modified glass fibers; S2. Components other than reactive interface-modified glass fiber are added from the main feed port of the twin-screw extruder. After the terminal amino PA66 melts, the reactive interface-modified glass fiber is added from the side feed port, so that the remaining carboxyl groups in its polyamide layer react with the amino end groups of the terminal amino PA66. Vacuum degassing is performed downstream of the location where the reactive interface-modified glass fiber is added. S3. The extruded molten material is stretched, cooled, and pelletized to obtain a coolant-resistant glass fiber reinforced PA material.

8. The preparation method according to claim 7, characterized in that, Step S1 includes: hydrolyzing an epoxy-containing silane and coating it onto the surface of a glass fiber, followed by a first drying process to obtain epoxy-containing silane-treated glass fiber; coating a dispersion containing dicarboxyl-terminated oligomeric PA66 onto the surface of the epoxy-containing silane-treated glass fiber, followed by a second drying and pre-reaction process to allow some carboxyl groups to react with epoxy groups while retaining the remaining carboxyl groups, thereby obtaining reactive interface-modified glass fiber.

9. The preparation method according to claim 8, characterized in that, The hydrolysate containing epoxy silane has an epoxy silane mass fraction of 0.5%–1.5%, a pH of 4.0–5.0, and a hydrolysis time of 20–40 min; the dispersion containing dicarboxyl-terminated oligomeric PA66 has a solid content of 8%–15%, and the dicarboxyl-terminated oligomeric PA66 accounts for 80%–92% of the dry matter of the dispersion; the second drying temperature is 110–130℃, and the pre-reaction temperature is 160–185℃ for 2–8 min.

10. The preparation method according to claim 7, characterized in that, In step S2, the melt temperature of the twin-screw extruder is 260–280°C, the screw speed is 250–600 r / min, and the vacuum degree is [missing information]. 0.080~ 0.095 MPa, melt residence time is 45-100 s.